2014
DOI: 10.1007/s11552-013-9547-0
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Proximal A2 and A4 Pulleys to Maintaining Kinematics in the Hand: A Biomechanical Study

Abstract: Our data provides evidence to the importance of the proximal portions of the A2 and A4 pulleys, and may support partial distal incision of these pulleys in certain clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…We observed that the centrally located annular pulleys A 2 and A 4 result in very high exion ranges (Tab. 2), thus agreeing with Dy and Daluiski (2013) and Chow et al (2014). Role of exible-inelastic biological C-pulleys is evident from sig-(a) Role of exible-inelastic C-pulleys and their heights: ℎ = ℎ 0 .…”
Section: The Biological Tendon Pulley Systemsupporting
confidence: 76%
See 2 more Smart Citations
“…We observed that the centrally located annular pulleys A 2 and A 4 result in very high exion ranges (Tab. 2), thus agreeing with Dy and Daluiski (2013) and Chow et al (2014). Role of exible-inelastic biological C-pulleys is evident from sig-(a) Role of exible-inelastic C-pulleys and their heights: ℎ = ℎ 0 .…”
Section: The Biological Tendon Pulley Systemsupporting
confidence: 76%
“…Annular pulleys are sti , while cruciate pulleys are exible but inextensible. Pulleys A 2 and A 4 are the most important for full range exion (Dy and Daluiski (2013); Chow et al (2014)). PP -proximal phalange, IP -intermediate phalange, DP -distal phalange.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical reconstruction of the A4 pulley is only advocated in cases of multilevel pulley injuries and outcomes seem to be disappointing. As Chow et al 7 have shown in cadaveric testing, insufficiency of the proximal A4 pulley has considerable effects on the range of motion of the proximal interphalangeal joint (PIP) joint, whereas effects on metacarpophalangeal joint or distal interphalangeal joint (DIP) joints were not significant. The functional integrity of the pulley system can be shown by physiological E-space, ensuring system efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…55 Proximal partial pulley excision may have a greater effect on digit range of motion than distal partial pulley excision. 56 To avoid the sequelae of A2 resection, reduction flexor tenoplasty has been reported. 57 Other authors have suggested "venting" of the A2 and A4 pulleys, either to facilitate repair or allow free gliding of the flexor tendons.…”
Section: Triggeringmentioning
confidence: 99%